A CROSS-SECTIONAL STUDY OF FACTORS CONTRIBUTING TO INCREASED HIV/AIDS PREVALENCE AMONG YOUTHS AT DR. RONALD BATTA MEMORIAL HOSPITAL, NSAMIZI-A, WAKISO DISTRICT. - MODOI JONAH WANGUSI; Glorious Orishaba (Student's Journal of Health Research, 2023)
Background:  The purpose of the study was to determine the factors contributing to increased HIV/AIDs prevalence among youths at Dr. Batta Memorial Hospital, Nsamizi-A, Wakiso District. The specific objectives were to find out individual, community, and health-related factors contributing to increased HIV/AIDS prevalence among youths at Dr. Batta Memorial Hospital, Nsamizi-A, Wakiso District. Methodology: The study employed a cross-sectional study design for quantitative data targeting a sample of 100 respondents who were youths using simple random sampling as the sampling tool and a semi-structured questionnaire as the data collection tool. Data was analyzed manually and presented in tables and figures using a Microsoft Excel computer program. Results:  Findings from individual factors that contributed to increased HIV/AIDs prevalence were; alcoholism (77%) and penetrative sex (78%). Results from community factors contributing to increased HIV/AIDs prevalence were; polygamy (60%) of respondents, ignorance about HIV sensitization (18%), and marriage (57%). Study findings from the health facility-related factors that contributed to increased HIV/AIDs prevalence showed that not testing for HIV (48%) and having unprotected sex (50.5%). Conclusion:  Based on the study findings, the following factors contributed to the biggest percentage increased prevalence of HIV/AIDS among youth alcoholism [77%], penetrative sex [78%], and polygamy (60%). Recommendation:  The researcher recommended that the government of Uganda through the Ministry of Health should put more emphasis on creating more awareness and sensitization about HIV/AIDs and its effects through holding continuous campaigns in communities, extending public health government programs to rural areas as well as funding external bodies involved in promoting HIV/AIDs awareness.